Assessment of breast carcinoma by correlating BI-RADS scoring with mammographic density - Dhadiala, Simranjit K.; Patankar, Shilpa (International Surgery Journal, 2020)
Background: Breast density assessed by mammogram expressed in percentage of density of breast tissue reflects variations in breast tissue composition and is strongly associated with increased risk of breast cancer. The BI-RADS density method was created to indicate whether a mammogram represents a negative, benign or suspected malignant finding. To assess breast carcinoma by correlating breast imaging-reporting and data system (BI-RADS) scoring with mammographic density. Methods: A total of 100 consecutive female patients with breast lump were assessed. The findings of the radiological examination and the histopathology results were subsequently analyzed to study the details of the breast disease in the group surveyed. BI-RADS classifications of breast density was extracted from mammography reports. Results: Majority of patients were having BI-RADS score 4 (33%) followed by BI-RADS score 5 (30%). Majority of the patients were having percentage breast density 4 (35%) followed by Percentage breast density 3 (28%). BI-RADS score and percentage breast density had statistically significant correlation (p<0.05). Conclusions: The BI-RADS score and percentage breast density by mammography had statistically significant correlation. Mammographic density is a strong breast cancer risk factor.